Design and Implementation of a Portable Air Quality Monitoring Device Using Nova Fitness SDS011 Sensor Technology in Urban Areas - Sirait, Naza Fahrul; Nengsih, Sri (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2026)
This study presents the design and implementation of a portable air-quality monitoring device based on the Nova Fitness SDS011 sensor to measure PM2.5 concentrations. The system integrates a microcontroller-based processing unit with real-time data display and audio warning features. Device performance was evaluated by calibrating against a reference instrument (BAM 1020, BMKG), yielding an average measurement error of 2.43%. In addition, validation by media experts indicated a high feasibility level of 95%, confirming the device’s suitability for practical use. Field testing conducted in several urban locations revealed significant variations in PM2.5 concentration, influenced by factors such as traffic density, industrial activity, and population distribution. The results demonstrate that the proposed device provides a reliable, low-cost, and portable solution for real-time PM2.5 monitoring in urban environments. This study contributes to the development of easy-to-use tools for monitoring air quality in support of environmental awareness and educational applications.